Anti‐SARS‐CoV‐2 vaccines in recipient and/or donor before allotransplant - Maxime Jullien; Marianne Coste‐Burel; Beatrice Clemenceau; Valentin Letailleur; Thierry Guillaume; Pierre Peterlin; Alice Garnier; Amandine Le Bourgeois; Berthe‐Marie Imbert; Jocelyn Ollier; Audrey Grain; Cyrille Touzeau; et al. (eJHaem, 2022)
Abstract The impact of pre‐transplant anti‐severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2) vaccine in 20 recipients of allogeneic hematopoietic stem cell transplantation (Allo‐HSCT) and/or their donors is reported here, showing that the persistence of anti‐SARS‐CoV‐2 antibodies can be detected in almost all patients, whatever the type of vaccine used, and up to 9 months post transplant. Also, an anti‐SARS‐CoV‐2 spike glycoprotein CD3+ T‐cell response could be detected in six (35%) of 17 evaluable patients. This study provides a rationale to consider anti‐SARS‐CoV‐2 vaccination of both recipients and donors before Allo‐HSCT.